Evaluation of the therapeutic effects of Aloe vera gel on minor recurrent aphthous stomatitis - Neda Babaee; Ebrahim Zabihi; Saman Mohseni; Ali Akbar Moghadamnia (Wolters Kluwer Medknow Publications, 2012)
Background: Aphthous ulcer is one of the most common diseases of the oral cavity with no known effective treatment so far, which could cause severe discomfort in patients. Aloe vera (A.V.) is a tropical plant with anti-inflammatory and immunostimulant effects, which could be of benefit in a diversity of wound healing conditions. The aim of this study is to evaluate topically administered A.V. gel on oral cavity minor aphthous healing. Materials and Methods: As a double-blind (case control) clinical trial, 40 patients with oral minor aphthous lesions were randomly allocated in either the case group (A.V. gel) or the control (placebo) group. The healing time (days after gel application), patient's pain score; the lesion and its surrounding inflammation diameters were recorded for 2 weeks. The obtained results were analyzed by either "Fishers exact" or t-student test using SPSS software. Results : The mean (±SD) of patients' age was 29.25 ± 8.48 and 27.95 ± 7.96 years in the control and A.V.-treated groups, respectively, which were not significantly different (P > 0.05). The duration of complete wound healing, pain score, wound size and inflammation zone diameter in the A.V.-treated group were significantly lower than the control group (P ≤ 0.05) on specific time points after treatment. Conclusion: It seems likely that A.V. 2% oral gel is not only effective in decreasing the recurrent aphthous stomatitis patients' pain score and wound size but also decreases the aphthous wound healing period.